Edukasi Literasi Keuangan Rumah Tangga sebagai Upaya Peningkatan Kesejahteraan di Dusun Awang Madya, Desa Giri Media - Ekawati, Ni Luh Juliani Rika; Lukman, Dwi Ratna Kamala Sari; Suarjaya, I Nyoman Alit; Yasa, I Komang Widya Purnama (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service Program (KKN) was carried out in Dusun Awang Madya, Giri Madia Village, focusing on financial literacy education to improve household welfare. The program was motivated by low financial literacy levels in rural communities, leading to weak financial management, consumptive spending, and lack of long-term planning. The objective was to increase children's and housewives' understanding of basic financial concepts, help them differentiate between needs and wants, and train them in simple budgeting. A participatory-educative method was applied through planning, socialization, training, and evaluation stages. The target group involved 15 children (elementary and junior high school students) and 10 housewives. Results showed that children could recognize income and expenditure, and distinguish needs from wants through games, while housewives were able to record household finances and draft short-term plans. The final evaluation indicated improved awareness and skills, although further assistance is required. Overall, the program significantly enhanced financial literacy and supported household welfare at the local level.